The virtues of the first Fatimid caliphs through the book elmajalis wa elmossayarat by Al-kadi Al-Numan between truth and myth - benzaoui, tarek (The Algerian Historical Journal, 2026)
This article aims to shed light on the most important pillar of the Ismaili Shia faith, namely the pillar of Imamate, through a critical analysis of what is stated in the book elmajalis wa elmossayarat by alkadi al-Numan, Through this work, he evoked the virtues of the first four caliphs of the Fatimid State in its Maghreb phase, The article also attempts to explain the Ismaili belief in their imams on the basis of what is transmitted from their books, and not from what is transmitted from others, And show the place of these virtues in relation to truth and myth. One of the most important results that the research reached is that the virtues of the imams of the sect raise them to a status that makes them intermediaries between the Creator and creation, so faith cannot be achieved without them. In the view of their opponents, these (virtues) are merely news that are subject to the test of the explicit mind, which places them in a position closer to superstition than to truth.